A new approach of three-dimensional guidance in paediatric cath lab: segmented and tessellated heart models for cardiovascular interventions in CHD - Ehret, Nicole; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert; Ruffer, Andre; Uder, Michael; Rompel, Oliver; Hammon, Matthias; Glöckler, Martin (Cardiology in the Young, 2018)
BACKGROUND: Optimal imaging is essential for catheter-based interventions in CHD. The three-dimensional models in volume-rendering technique currently in use are not standardised. This paper investigates the feasibility and impact of novel three-dimensional guidance with segmented and tessellated three-dimensional heart models in catheterisation of CHD. In addition, a nearly radiation-free two- to three-dimensional registration and a biplane overlay were used.Methods and resultsWe analysed 60 consecutive cases in which segmented tessellated three-dimensional heart models were merged with live fluoroscopy images and aligned using the tracheal bifurcation as a fiducial mark. The models were generated from previous MRI or CT by dedicated medical software. We chose the stereo-lithography format, as this promises advantage over volume-rendering-technique models regarding visualisation. Prospects, potential benefits, and accuracy of the two- to three-dimensional registration were rated separately by two paediatric interventionalists on a five-point Likert scale. Fluoroscopy time, radiation dose, and contrast dye consumption were evaluated. Over a 10-month study period, two- to three-dimensional image fusion was applied to 60 out of 354 cases. Of the 60 catheterisations, 73.3% were performed in the context of interventions. The accuracy of two- to three-dimensional registration was sufficient in all cases. Three-dimensional guidance was rated superior to conventional biplane imaging in all 60 cases. We registered significantly smaller amounts of used contrast dye (p<0.01), lower levels of radiation dose (p<0.02), and less fluoroscopy time (p<0.01) during interventions concerning the aortic arch compared with a control group. CONCLUSIONS: Two- to three-dimensional image fusion can be applied successfully in most catheter-based interventions of CHD. Meshes in stereo-lithography format are accurate and base for standardised and reproducible three-dimensional models.
EVALuna2:34698